Smear layer removal and collagen fiber exposure using tetracycline hydrochloride conditioning - Ishi, Eduardo de Paula [UNESP]; Dantas, Andréa Abi Rached [UNESP]; Batista, Luiz Henrique Carvalho; Onofre, Mirian Aparecida [UNESP]; Smapaio, José Eduardo C. [UNESP] (My University, 2008)
Aim: Smear layer removal and collagen fiber exposure may improve periodontal treatment and regeneration. This in vitro study assessed smear layer removal and collagen fiber exposure after tetracycline hydrochloride (TTC) application on root surfaces using scanning electron microscopy (SEM). Methods and Materials: Root cementum was removed with diamond burs followed by scaling and root planning. Four hundred fifty samples were divided into ten groups: a control (saline application) and nine different TTC concentrations were applied at doses of 10, 25, 50, 75, 100, 125, 150, 200, and 250 mg/ml. The TTC application was performed in all groups in three different ways (passive, brushing, and burnishing) and at three different periods of conditioning (1, 2, and 3 minutes). A previously trained, calibrated, and blind examiner evaluated photomicrographs of the samples using Sampaio's index (2005). Statistical analysis was performed using the Kruskal-Wallis' and Dunn's tests. Results: The concentrations of 50 mg/mL and 75 mg/mL applied by burnishing were the most effective in smear layer removal and collagen fiber exposure. Both the passive mode of application (p=0.0001) and 1 minute period of application (p=0.002) were the least effective. Conclusions: The concentrations of 50 mg/mL and 75 mg/mL applied by burnishing during 2 or 3 minutes were the most effective. Clinical Significance: These parameters may be applied in periodontal procedures involving TTC root conditioning to optimize results.
Keywords: Periodontics; SEM; Smear layer; Tetracycline hydrochloride; antiinfective agent; fibrillar collagen; tetracycline; cementum; dental surgery; dose response; drug effect; histology; human; methodology; preventive dentistry; scanning electron microscopy; ultrastructure; Anti-Bacterial Agents; Decalcification Technique; Dental Cementum; Dose-Response Relationship, Drug; Fibrillar Collagens; Humans; Microscopy, Electron, Scanning; Root Planing; Smear Layer; Tetracycline